Pure and Mixed Desmoplastic Melanomas: A Retrospective Clinicopathologic Comparison of 33 Cases. (27th November 2021) - Chu, Sherman; Schrom, Kory P.; Tripathi, Raghav; Conic, Rosalynn R. Z.; Ezaldein, Harib H.; Scott, Jeffrey F.; Honda, Kord
Abstract : Background: Pure and mixed desmoplastic melanomas (DMs) may have different natural histories and behaviors. Methods: We conducted a retrospective review of patients diagnosed with DM at our institution between January 1997 and April 2019. A total of 33 unique DMs were identified and subsequently analyzed based on the histologic type (pure vs. mixed). Results: The majority (57.6%) of our cases were classified as pure histology. Patients with pure DMs were more likely to be men ( P = 0.035) and be older than 65 years ( P = 0.019) compared with patients with mixed DMs. Patients with mixed DM were more likely to have mitoses present ( P = 0.001) compared with patients with pure DM. There were no differences in ulceration, perineural invasion, vascular invasion, or survival between patients with pure and mixed histologic subtypes. In addition, no differences in sentinel lymph node biopsy, radiation, or chemotherapy were noted between the 2 histologic subtypes. Immunohistochemistry showed that 27.3% of the pure DMs stained with Melan-A and HMB45 were positive for these immunomarkers. Conclusions: Pure and mixed variants of DM were found to have similar clinicopathologic characteristics. Patients with the mixed histologic subtype were more likely to have mitoses, but no difference in the therapeutic management or patient survival was seen between the 2 subtypes.